Fear of Сoronavirus Disease (COVID-19) and Basic Personality Beliefs - Gritsenko V.V.; Reznik A.D.; Konstantinov V.V.; Marinova T.Y.; Khamenka N.V.; Isralowitz R. (Клиническая и специальная психология, 2020)
The article presents data on the experience of fear about the coronavirus disease (COVID-19), depending on the severity of personality basic beliefs. Authors interviewed 950 people aged 12 to 74 years (average age is 35 years). The study was conducted in March 2020 online. The intensity of fear about the coronavirus was studied using the COVID-19 fear scale developed by a team of scientists from Hong Kong, Iran, the United Kingdom and Sweden. The scale was tested for reliability and validity in the Iranian, Russian and Belarusian samples (Ahorsu D.K. et al., 2020; Reznik A. et al., 2020). The personality basic beliefs were diagnosed using the Scale of Basic Beliefs developed by R. Janoff-Bulman (translation and adaptation by O.A. Kravtsova) (Soldatova G.U. et al., 2008). Revealed that more than a third of the subjects have a high level of fear about the coronavirus. Showed that the low intensity of fear about the COVID-19 disease is associated with the severity of personality basic beliefs. Concluded that the personality basic beliefs in goodness and justice of the world around, the values and importance of own “Self” can act as psychological resources for coping a tough situation in life, the specificity of which is due to the fear about the coronavirus disease.